2023
DOI: 10.1177/15396754221143446
|View full text |Cite
|
Sign up to set email alerts
|

Public sectors and nonprofit organizations use of social media to communicate compassion during crisis

Abstract: Using compassion is an important public communication strategy associated with many positive outcomes. While research on compassion has grown in many fields, few studies have explored the role of compassion in crisis communication. This study fills the gap in the research to examine if public sectors and nonprofit organizations used compassion on their social media content and how it impacts public emotion in a winter freeze crisis in Texas. Facebook posts from four local agencies were analyzed to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…A. (2023) (23) , examine the Facebook messages from four local organisations during a Texas winter freeze crisis, this research investigated the role of compassion in crisis communication. The findings demonstrated that compassion-themed Facebook messages greatly increased online public interaction, reduced negative emotions, and boosted positive emotions.…”
Section: Rd Pillar: Dependent Variable: Media In Crisis Managementmentioning
confidence: 99%
“…A. (2023) (23) , examine the Facebook messages from four local organisations during a Texas winter freeze crisis, this research investigated the role of compassion in crisis communication. The findings demonstrated that compassion-themed Facebook messages greatly increased online public interaction, reduced negative emotions, and boosted positive emotions.…”
Section: Rd Pillar: Dependent Variable: Media In Crisis Managementmentioning
confidence: 99%